Q: If 2x plus 3x equals 5x 2k plus 3k equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2k - 3k - m + 2m = -k + m

When factored it is: (3k+5)(k-1)

-4. -3k+10=k+2.... First we have to move the K to one side -3k+10=k+2 __________ This will reduce -3k to -2k and k+2 to just 2 K -2k+10=2 Now we have to subtract 10 to both sides as to get k alone. -2k+10=2 ________ Now we should have -2k on one side and 2-10 on the other. -10 -2k=2-10....... 2-10= 8. We have to get -2k into just K on itself so we divide by 2. -2k=-8 ______ Your answer is 4. You have to do one side what you do the other. 2

The above expression can be simplified to:14n-2k

It simplifies to 7k = 49 which gives k = 7.

Related questions

k=4

==> 3k+14=k ==>3k-k=-14 ==>2k=-14 ==>k=-7 ans...

2k - 3k - m + 2m = -k + m

3k-1=k+2 2k=3 k=3/2=1.5

It can be simplified to: 9k

When factored it is: (3k+5)(k-1)

-4. -3k+10=k+2.... First we have to move the K to one side -3k+10=k+2 __________ This will reduce -3k to -2k and k+2 to just 2 K -2k+10=2 Now we have to subtract 10 to both sides as to get k alone. -2k+10=2 ________ Now we should have -2k on one side and 2-10 on the other. -10 -2k=2-10....... 2-10= 8. We have to get -2k into just K on itself so we divide by 2. -2k=-8 ______ Your answer is 4. You have to do one side what you do the other. 2

The above expression can be simplified to:14n-2k

3k+16 = 5k subtract 3k from both sides 16 = 2k divide both sides by 2 8 = k

It simplifies to 7k = 49 which gives k = 7.

2k = 5k-30 Subtract 5k from both sides: -3k = -30 Divide both sides by -3 to find the value of k remembering that a minus divided into a minus becomes a plus: k = 10

3k + 3 = 8 3k = 8 -3 3k = 5 k = 5/3